Digital Material EPUB Based to Understand Tarkib: Is Flipped Classroom Effective? - Riwanda, Agus; Ridha, Muhammad; Islamy, M. Irfan (Universitas Islam Negeri Raden Intan Lampung, 2021)
Flipped Classroom strategy is blended learning that build students learning autonomy. However, student learning outcomes in X IPA 2 class of MAN 4 HST on tarkib material is still below the passing grade. Arabic is important to be mastered for better understanding in Islamic teaching from its sources. This study aimed to see and compared the students learning outcomes between the flipped classroom strategy with epub digital book teaching material and traditional strategy. Experimental research was used with a non equivalent control group design and intact group. The experimental class was X IPA 2 which consisted of 26 students and the control class was X IPA 1 which consisted of 29 students. The data were collecting from pretest, treatment, and posttest on the control and experimental class. The results of this study was found out which there was significant difference in the acquisition of learning outcomes. The experimental class which used digital book had better average learning outcomes than the control class which used conventional strategies. The significance value asymp. Sig (2-tailed) was 0.200 which was higher than 0.05. So, there was a significant different from the results of the control and experimental class. This study also rejected that the flipped classroom strategy which was assisted with digital material which based on epub did not gain the significant result or better attitudes rather than the non-flipped classroom. This study contributed to enhancing the learning quality of Arabic in non-language class.